Influence of eye diseases on the retina and iris pattern recognition and its significance in the early ophthalmic diagnosis - Saeed, Emil; Konopińska, Joanna; Mariak, Zofia; Saeed, Khalid (Klinika Oczna / Acta Ophthalmologica Polonica, 2017)
The state of the art in the field of biometrics focused on retina, iris pattern recognition and their practical applications in forensics and airports are discussed in this paper. The confounding effect of ocular diseases on ocular pattern recognition is possible, which has been extensively discussed here, considering that neither the scope of this effect has been known nor respective retinal imaging standards have been developed. The paper is based on the own research of human iris and retina in biometrics carried out as a cooperation between medical and IT specialists. The paper aims at providing satisfactory answer to two key questions: 1. Can patients with anomalies of the iris and/or the retina be reliably identified using biometric properties of the discussed structures, and 2. When is it possible (under certain conditions) and when absolutely excluded.